The Carotid Intima Medial Thickness Among Type 2 Diabetes Mellitus and Controls: A Cross Sectional Study - EDAFE, EMMANUEL AUCHI; Akpa, Maclean R (International Journal of Innovative Research in Medical Science, 2024)
Introduction: In Nigeria, the prevalence of diabetes mellitus has been on increasing steadily. With the increasing prevalence of diabetes mellitus, one expects higher rate of its complications including carotid atherosclerosis (which may present with silent infarct, transient ischemic attack, or ischemic stroke) and coronary artery disease. The common link between carotid atherosclerosis and coronary artery disease is atherosclerotic cardiovascular disease with increase intimal medial thickness. This study evaluated medial intima thickness of among Diabetes at the University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria. Methods and Materials: The study was a descriptive cross-sectional, to assess relationship between peripheral artery disease and carotid atherosclerosis among type 2 diabetic subjects in UPTH using the ankle brachial pressure index and carotid intima-medial thickness. 110 diabetic subjects, and 110 age and gender matched non-diabetic, controls were recruited for the study. Type 2 diabetic subjects and controls that met the inclusion criteria and consented were recruited consecutively as they met the inclusion criteria. Demographic data, anthropometric measures were taken and recorded. Using a structured questionnaire, information on medical history, physical examination and examination of carotid intima-medial thickness were measured and documented. Confidentiality was maintained throughout the 13 months period of the study. Data obtained were checked for errors and corrected before being analyzed using the statistical package for social sciences software 20.0 (SPSS 20.0). Results: There were 67 females and 43 males with type 2 diabetes, while 61 Females and 49 males served as controls. The mean age for the diabetic subjects was 54.85 ± 10.09, while that for the controls was 52.86 ± 10.31. The mean duration of diabetes mellitus was 6.24 ± 4.53. The patient with CIMT more than 1mm account for 19.1% of the subjects, while the controls had 7.3% Th is statistically significant with a p-vale of <0.001. Increased thickness of the carotid intima-medial was found to be significantly associated, increasing duration of diabetes. Conclusion: CIMT is more common in diabetic patients compared to age and gender-match controls. Most subjects with increased CIMT are asymptomatic.